The Animals in the Cantigas de Santa Maria (II) - de Carvalho Mendes, Augusto (Eikón / Imago, 2016)
In this paper we analyzed the representation of animals in the Cantigas de Santa Maria, a poetry composed by the king Don Alfonso X the Wise. To do so, we selected all the passages of the Cantigas de Santa Maria concerning animals and compared with ancient and medieval texts relating to them. After a systematic study of both the texts and the rich illuminations that accompany them, we concluded that the animals are represented in the Cantigas de Santa Maria in a realistic way, opposed to symbolic way, very common in the medieval period. This characteristic observed in the work in question is full of consequences. One of them is that this systematic study corroborates the thesis that the Cantigas de Santa Maria are part of Gothic literature. Finally, we try to articulate the Gothic vision of the world with a scientific worldview.